Moisture content and oxidative damage determine longevity of the seeds of potential cash crop halophyte Haloxylon stocksii. (2nd November 2022) - Abbas, Sahar; Rasheed, Aysha; Soriano, Pilar; Estrelles, Elena; Gul, Bilquees; Hameed, Abdul
Abstract: Haloxylon stocksii is a succulent halophyte with high potential to become edible-oil and medicinal crop for the arid-saline lands. Studies about germination ecology and mechanisms of salinity tolerance during vegetative stage of this plant exist. However, information about longevity and biochemical changes in H. stocksii seeds during storage is absent. This study thus examined longevity, and physio-chemical attributes of the H. stocksii seeds under different storage conditions. Fresh seeds were non-dormant with ∼96% germination in water. Storage of seeds for four months had little effect on their germination in most conditions. However, storage for 8 or 12 months caused a complete germination inhibition in laboratory and field respectively. Seed moisture increased with the storage time and was positively correlated with mortality. Antioxidant activity of the seeds increased with time in all conditions, which however was inadequate to prevent oxidative damage as hydrogen peroxide and lipid peroxidation levels increased, especially with >4 months of storage. Hence, these data indicate the short longevity of the H. stocksii seeds resulting from moisture-induced oxidative damages during storage.